Schools as Artifacts: Critical Autoethnography and Teacher Renewal - Benoit, Brian (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
This article examines how past memories can shape how we see the present and future in the context of teacher education and professional development. Using qualitative inquiry, drawing in particular on self-study and memory-work, I explore the ways in which critical autoethnography can serve as a tool for personal and professional growth in the context of teacher identity.